Thermodynamic and Spectroscopic Properties Investigation of Coronene as a Function of the Number of Oxygen Atoms and Temperature via Density Functional Theory - Khalaf, Taif Talib; Hussein, Mohammed T. (Iraqi Journal of Physics, 2024)
The study focused on the thermodynamics characteristics such as (Gibbs free energy, heat capacity, entropy and enthalpy) and spectroscopic properties like (IR spectra, reduced masses, and force constant) of coronene (C24) and reduced coronene oxide (C24OX) where X =1–5 as a function of number of oxygen atoms and temperature from (298-398) oK. Density functional theory was used in the methodology with the basis sets 6-311G** and the hybrid functional B3LYP (Becke, 3-parameters, Lee-Yang-Parr), utilizing the Gaussian 09W program. Gaussian view 05 was used as a complementary program to calculate the geometrical structures. The Gibbs free energy and enthalpy decrease (negative sign) with increased oxygen atoms and temperature, indicating an exergonic reaction. The entropy and heat capacity increased with the number of oxygen atoms and temperature. The spectroscopic characteristics were compared with experimental results, particularly the longitudinal optical modes of vibration for graphene and graphene oxide (1585 - 1582) cm-1, which were in good agreement.